Basic pension recipients are more likely to be employed than other pensioners - Hermann Buslei; Johannes Geyer; Peter Haan; Lukas Harder (DIW Weekly Report, 2025)
With the 2021 introduction of Germany's basic pension, longterm insured persons with low incomes can receive a supplement to their statutory pension. In 2024, around 1.4 million recipients received an average pension increase of 100 euros as a result. Data from the German Pension Insurance show that women especially benefit from the basic pension supplement. At the same time, it is striking that people entitled to a basic pension are more likely to remain active in the labor market while receiving their old-age pension. The majority of them hold marginal jobs. It has been observed that all pensioners are particularly likely to continue working if they were still employed in the last year before retirement. Among basic pension recipients, the proportion of those in employment is even higher. The planned "Aktivrente" includes a tax allowance that could positively affect employment in this group; consequently, it should be excluded from the earnings test. Additionally, the growing number of basic pension recipients should be closely monitored. Politically, the primary goal is to ensure that fewer people are dependent on this supplement after a long working career.
Keywords: H55; J22; J26; 330; Employment; Silver worker; Basic pension; Redistribution